Hubungan Tingkat Pengetahuan dengan Perilaku Pencegahan Toksoplasmosis pada Ibu Usia 15-49 Tahun - Afina, Nadia Mayra; Mediana, Dian (Fakultas Kedokteran Universitas Trisakti, 2022)
BACKGROUND Toxoplasmosis is an infectious disease caused by the parasite Toxoplasma gondii. In Indonesia, the number of positive T. gondii findings in humans was around 53%. The transmission of toxoplasmosis from animals to humans can be through food, such as consumption of undercooked meat or raw vegetables or gardening without using gloves. Toxoplasmosis infection in women of childbearing age, especially during pregnancy, will be dangerous because it can cause premature birth, spontaneous abortion, fetal death, or babies born with congenital toxoplasmosis. This study investigates the relationship between knowledge level and toxoplasmosis prevention behaviour. METHODS This study uses a cross-sectional analytic observational study design on mothers aged 15-49 years at Puskesmas Grogol Petamburan, Jakarta, in November-December 2021. The samples studied were 132 samples. Data was collected using a knowledge level questionnaire about toxoplasmosis containing 20 statements and a toxoplasmosis prevention behaviour questionnaire containing eight statements. Data were analyzed by chi-square statistical test SPSS with significance limits of p<0.05. RESULTS Of the 132 respondents who participated in this study, 46 respondents (34.8%) had a good level of knowledge (score ≥ 8), while 86 respondents (65.2%) had a poor level of knowledge. A total of 91 respondents (68.9%) had very good preventive behavior, 26 respondents (19.7%) had good preventive behavior, and 15 respondents (11.4%) had poor preventive behavior. The chi-square statistical test results showed no significant relationship between the level of knowledge and toxoplasmosis prevention behavior (p=0.867). CONCLUSION Toxoplasmosis preventive behavior in women of childbearing age at Grogol District Health Center was not depend on the level of knowledge of toxoplasmosis. Toxoplasmosis preventive behavior may be related to other factors that require further research. KEYWORDS: Knowledge, Prevention Behavior, Toxoplasmosis, Childbearing Age